The Influence of Data Strategy on Competitive Advantage and Company Performance (Empirical Study on Engineering, Procurement, and Construction Companies) - Andry, Elvi; Pracoyo, Anto; Simatupang, Batara Maju; Karambut, Fermico (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Data strategy is an important point for a company in the era of digitalization because it can be used as the main source for increasing a company's competitive advantage, which will ultimately improve the company's performance. This research aims to see the influence of data strategy on competitive advantage and company performance. Data strategies here are divided into two, namely defensive data strategies and offensive data strategies. The research was conducted with a survey of 202 respondents from EPC companies listed on the Indonesia Stock Exchange. Using the Structural Equation Modeling (SEM PLS) the research results found that defensive data strategies and offensive data strategies influence competitive advantage but not Company Performance. The results also explain that data strategy does not mediate the relationship between offensive and defensive data strategies with competitive advantage and company performance. This research provides implications for company policy in formulating strategies by considering the position of defensive data strategies and offensive data strategies because they can directly and positively influence competitive advantage. Practically, the implications of the results of this research can help EPC companies in designing data policies or strategies and using them as a competitive advantage.